2019
DOI: 10.1029/2019gl083437
|View full text |Cite
|
Sign up to set email alerts
|

The Fragmented Death of the Farallon Plate

Abstract: The processes that accompany the death of an oceanic plate, as a ridge nears a trench, remain enigmatic. How the plate might reorganize, fragment, and eventually be captured by one of the bounding plates are among the unresolved details. We present a tomographic model of the Pacific Northwest from onshore and offshore seismic data that reveals a hole in the subducted Juan de Fuca plate. We suggest that this hole is the result of a tear along a preexisting zone of weakness, is causing volcanism on the North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…For simplicity, we infer in our slab model that the slab is continuous and coherent in the lower mantle, but we are unable to rule out the possibility that the relative incoherency of the slab anomaly is not representative of true slab structure. A fragmented slab at these depths is feasible given the variety of recent studies identifying fragmented slabs in both the upper and lower mantle in other subduction zones (Hawley & Allen, ; Obrebski et al, ; Peng et al, ; Portner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, we infer in our slab model that the slab is continuous and coherent in the lower mantle, but we are unable to rule out the possibility that the relative incoherency of the slab anomaly is not representative of true slab structure. A fragmented slab at these depths is feasible given the variety of recent studies identifying fragmented slabs in both the upper and lower mantle in other subduction zones (Hawley & Allen, ; Obrebski et al, ; Peng et al, ; Portner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several workers attribute the High Lava Plains trend to mantle upwelling associated with slab rollback (e.g., Long et al, 2009;Ford et al, 2013), but this may be difficult to reconcile with evolving seismic data that reveal a shortened and highly fragmented slab in this region (Long, 2016). Slab fragmentation is described by Hawley and Allen (2019) as a propagating tear responsible for westward mantle flow beneath the High Lava Plains trend. Following Jordan et al Colgan and Henry (2009).…”
Section: Coeval Rhyolite Migrations Along Opposing Trends (10 Ma To Rmentioning
confidence: 99%
“…Segmentation of slab high-velocity anomalies at depth appears to be a robust feature but it is unclear what the exact spatial extent is, an important distinction to understanding if this is a tear, a large gap, or an imaging artifact. The most robust reduction in both models at 45°N places a segment boundary further to the north than suggested by recent S-wave imaging (Hawley & Allen, 2019).…”
Section: Comparison Of P-and S-wave Structurementioning
confidence: 59%
“…High‐velocity anomalies tend to decrease in amplitude beneath Oregon. Some have attributed this to a slab‐plume interaction (Geist & Richards, 1993; Obrebski et al., 2010) and/or a tear in the slab (Hawley & Allen, 2019), while others have suggested that it is an imaging artifact (Roth et al., 2008). If the slab is nonexistent in this region, that has implications for dynamic models relying on slab rollback to drive mantle circulation (Long, 2016).…”
Section: Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation